The reality of financial inclusion in the Arab countries and the role of financial technology in promoting it (country experiences) - abderrahim, Leila; beldjilali, Fatiha (Journal of Research in Finance and Accounting, 2022)
This study aims to highlight the importance of financial inclusion in promoting economic growth and the stability of the financial system, while standing on the reality of financial inclusion in a group of Arab countries and the role of financial technology in promoting it, by analyzing financial inclusion indicators and highlighting the role of financial technology companies in providing many financial services and their contribution to Supporting economic diversification efforts and policies. We adopted the analytical approach using a number of forms to illustrate the development of indicators of financial inclusion and financial technology techniques used in the Arab countries, and concluded the need to adopt a comprehensive strategy aimed at relying on digital payments and financial technology as a main tool to enhance financial inclusion and the transition to a non-monetary economy, by modernizing the communications infrastructure. And preparing a law to develop non-cash financial transactions under the umbrella of central banks, in addition to approving regulatory frameworks that achieve integration between information and communication technology and the financial sector.